The prediction of success in kickboxing based on the analysis of morphofunctional, physiological, biomechanical and psychophysiological indicators - L.V. Podrigalo; A.A. Volodchenko; O.A. Rovnaya; O.V. Podavalenko; T.I. Grynova (Physical Education of Students)
Purpose: To substantiate and develop a methodology for predicting success in kickboxing on the basis of analysis of morphofunctional, physiological, biomechanical and psychophysiological indicators. Material: it was examined athletes of kickboxing (n=185, age 18.58 +- 0.46 years). It was studied the features of physical development (n = 18). The main biomechanical parameters (n=45) were determined. Goniometric indices of limb joints (n=29) were studied. It was studied the features of psychophysiological reactions (n =76). The adaptive capabilities of the cardiovascular system were studied (n=17). The prognostication is carried out by means of a sequential Wald procedure. Prognostic coefficients and their informativity were calculated. Results: a prognostic table was developed containing the indicators of the functional state of kickboxing athletes. The table includes 31 criteria, the informativeness of which varied within 115,45 - 2,23. The content of the forecast consists in: an evaluation of the results; determination of the corresponding prognostic coefficient; summation of coefficients. The threshold was set at the level +- 13, which corresponds to a probability of 95% (p<0,05). Exceeding the positive threshold means a high level of success for the athlete. When the negative threshold is reached, the probability of success is low. Conclusions: The proposed methodology is based on a sequential analysis of Wald. The technique is a simple, informative and objective tool for monitoring and predicting the status of athletes.